Nation of Islam dan Hak Sipil Kaum Kulit Hitam di Amerika Serikat (1930-1976) - Tia Oktarina (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
The Nation of Islam is a black organization that uses Islamic principles in its movement, the main goal of which is the freedom of black civil rights. The Nation of Islam has become a place of hatred for blacks against whites because of the racial discrimination they have experienced so far. Many researches on the civil rights of blacks in the United States have been written, but the struggle for civil rights by the Nation of Islam is still lacking, especially in Indonesia. The main discussion of the research is "how were the efforts made by the Nation of Islam in fighting for the civil rights of black people in the United States from 1930-1976?" by using historical research methods (historical methods) which include heuristics, source criticism, interpretation, and historiography, with library research techniques in collecting data. The concept used in analyzing this thesis is the concept of messianism, racial discrimination, ethnocentrism, and human rights (HAM) which will explain the background of the formation of the Nation of Islam, the efforts made by the Nation of Islam in fighting for the civil rights of black people from 1930 to 1976, and the impact of the struggle of the Nation of Islam on the civil rights of black people in the United States. The results of this study indicate that the purpose of establishing the Nation of Islam is to save the lives of black people in the United States from all forms of racial discrimination, segregation, and negative stereotypes that lead to the struggle for civil rights. The efforts made by the Nation of Islam are restoring the identity and confidence of the African-American race, developing an independent economy, and establishing relations with other countries. Then the impact that the Nation of Islam had on its struggle for civil liberties was to raise the status of blacks socially and economically, to build a number of black assets in the form of shops, restaurants, schools, land, and a newspaper called Muhammad Speaks.Keywords: Black People, Nation of Islam (NOI), Civil Rights Struggle